2020
DOI: 10.1590/0037-8682-0351-2020
|View full text |Cite
|
Sign up to set email alerts
|

Sequential serological surveys in the early stages of the coronavirus disease epidemic: limitations and perspectives

Abstract: Introduction: Estimates of the number of individuals infected by severe acute respiratory syndrome coronavirus 2 are important for health planning and establishment of expectations regarding herd immunity. Methods: Seven testing rounds of a serological survey were conducted at 1-week intervals between April 19 and May 31, 2020 in Teresina municipality. Results: Over the 7 weeks, serological positivity increased from 0.56% (95% confidence interval [CI]: 0.18%-1.30%) to 8.33% (95% CI: 6.61%-10.33%), representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 2 publications
0
14
0
2
Order By: Relevance
“…The vast majority of studies (n=25; 67.6%) reported only antibody testing, while the exclusive use of RT-PCR were presented in 5 (13.5%), and both tests were conducted in 7 (32). Two studies showed overall unclear risk of bias (34,49).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The vast majority of studies (n=25; 67.6%) reported only antibody testing, while the exclusive use of RT-PCR were presented in 5 (13.5%), and both tests were conducted in 7 (32). Two studies showed overall unclear risk of bias (34,49).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors seem to have not been concerned with managing this issue because even though the response rate was low, there was still an adequate sample (23,35,36,40,42). Repeated crosssectional studies featured a widely distinct prevalence estimate on each round (29,36,49,50). This trend might be caused by the ascending curve of infected people, following the epidemic's natural course.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IgM testing has been designed and validated, but currently limited information is available about the performance of these tests (48). Some tests may produce inaccurate results (49), suggesting gold immunochromatography assay and ELISA methods should be used to eliminate or reduce the impact of cross-reaction. Serological testing is helpful for preliminary screening of suspected and high-risk groups (50).…”
Section: Clinical Manifestations and Diagnosismentioning
confidence: 99%